Internal and External Factors Influencing Oral Communication Performance Among English Education Majors: A Qualitative Study in Indonesian Higher Education - Hariyanto; Chusnu Yuli Setyo; Husen; Ariel Sharon (Reforma: Jurnal Pendidikan dan Pembelajaran, 2026)
As a critical competency in second-language acquisition, English speaking proficiency is essential for effective communication. While frequently evaluated through oral presentations, many learners encounter significant obstacles that hinder their performance. Consequently, this study aims to identify the internal and external factors influencing the speaking performance of English Education majors within an Indonesian higher education context. Employing a qualitative descriptive approach, data were collected through questionnaires, classroom observations, and document analysis involving 13 second-semester English Education students at Universitas Islam Lamongan. The findings reveal that students' oral communication is hindered by intertwined internal and external variables. Internal factors comprise psychological barriers predominantly fear of errors, embarrassment, and low self-confidence—alongside linguistic challenges, including native language interference, limited vocabulary, and incorrect pronunciation. External factors encompass unsupportive classroom environments and limited English exposure outside formal settings. Participant feedback indicated that addressing these factors through structured pedagogical interventions, such as Vygotskian scaffolding, supportive classroom environments, and constructive feedback, significantly reduces anxiety and enhances overall speaking proficiency.